Risk factors for the femoral head aseptic necrosis development in patients with systemic lupus erythematosus - I. G. Kushnareva; T. V. Popkova; M. A. Makarov; A. E. Khramov (Современная ревматология)
Objective: to identify risk factors for the development of the femoral head aseptic necrosis (FHAN) and osteoarthritis (OA) of the hip joint (HJ) in patients with systemic lupus erythematosus (SLE) according to a retrospective analysis.Material and methods.The retrospective study included data from the case histories of 103 patients with SLE who underwent total hip arthroplasty (HA) (unilateral in 82 patients, bilateral in 21). The total follow-up period ranged from 2 years to 21 years. Among the patients included in thestudy, the majority were women (86.4%), the ratio of women and men was 7:1. At the time of surgery, the average age of women was 36.3±13.25 years, men – 36.2±9.57 years, duration of the disease – 168.0±132.5 months. SLE activity was assessed using the SLEDAI-2K scale. All patients were taking glucocorticoids (GC). The average duration of GC treatment was 89.0±87.2 months. 71.8% of patients received immunosuppressive therapy: hydroxychloroquine – 55.3%, azathioprine – 10.7%, methotrexate – 5.8%. The functional status of hip joint was determined using the Harris scale; by the time of surgery, the average score was 45.6±13.1 points. Pain intensity was assessed using a visual analogue scale and reached an average of 70.1±16.0 mm.Results and discussion. In 58.5% of patients with SLE, the indication for HA was FHAN (Group 1) and in 41.6% – OA of HJ (Group 2). At the time of HA, the duration of the disease was longer and the age was higher in group 2 than in group 1 (p<0.05). An analysis of individual clinical manifestations of SLE that preceded the development of HJ pathology revealed that arthritis and the presence of an antinuclear factor, ANF, were associated with the development of FHAN (p=0.022 and p=0.04, respectively). At the onset of the disease, patients of the 1st group, compared with patients of the 2nd group, more often had lesions of the skin, kidneys and serositis (22.9 and 20.5%; 14.5 and 11.7%; 68.7 and 64.7 %, respectively), but they were less likely to have mucous membranes and the central nervous system (CNS) involvement (14.5 and 23.5%; 10.4 and 17.6%, respectively). However, these differences did not reach statistical significance. Almost all of these disease manifestations, with the exception of the mucous membranes and the CNS lesions, were more often observed in patients with the development of FHAN, which indicates a higher activity of the disease at the onset of SLE. At the time of HA, we did not find any relationship between SLE activity and FHAN formation and hip OA. Patients of the 1st and 2nd groups in the same number of cases had mild (56.2 and 58.8%, respectively) and moderate (35.4 and 32.4%, respectively) activity according to SLEDAI-2K. No activity (SLEDAI-2K – 0 points) was also observed in patients of both groups with the same frequency (8.3 and 8.8% of cases, respectively). Associations of cumulative and daily doses of GC with the development of FHAN and OA of HJ were not revealed. In the 1st group, the average daily dose of GC was slightly higher, and the cumulative dose was less than in the 2nd group (8.59±4.75 and 7.79±5.39 mg; 20.0±11.9 and 23.8±19.2 g, respectively), but these differences were not significant (p>0.05).Conclusion. In SLE patients, the incidence of FHAN and HJ OA was comparable. At the time of HA, SLE patients with HJ OA were older and had a longer duration of the disease than patients with FHAN. The risk factors for FHAN were arthritis and ANF positivity at the onset of SLE.